Ministry of Electricity and Renewable Energy Ministerial Decree No. 8 of the Year 2023 Issued on 9/1/2023 = وزارة الكهرباء والطاقة المتجددة قرار وزارى رقم 8 لسنة 2023 صادر بتاريخ 9/1/2023 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic